Kepuasan Kerja Sebagai Variabel Mediasi Dalam Pengaruh Keadilan Organisasi Terhadap Komitmen Organisasi - Pratama, Arie (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study is to determine the relationship between organizational commitment and organizational fairness. With job satisfaction as a mediator, this study tested the following three hypotheses: 1) Job satisfaction has an impact on organizational commitment, 2) job satisfaction has an impact on organizational fairness, and 3) job satisfaction as a mediator between organizational fairness and organizational commitment. dissemination of questionnaires to respondents directly as a means of data collection. The respondents to this study were employees of PT. Jakarta, Borneo Across the World. There were 98 questionnaires given. The reliability and validity test is the test method. Performs a direct linear regression test on the first and second hypotheses. Path analysis is used to calculate the influence of mediation in testing the third hypothesis. Job satisfaction has a mediating effect on organizational fairness and organizational commitment, according to ding with the research findings, and organizational commitment is influenced by organizational fairness variables.